Im Orbit einstellbare Ausgangsfilter und -multiplexer - Arnold, Christian (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2017)
Generally, communication satellites do not allow to flexibly react to changes in demand. This work presents theoretical and practical principles allowing to flexibly reconfigure the frequency plan of an output multiplexer. Particularly, based on the investigations performed in this work for the first time it is possible to realize manifold-based multiplexers with multiple channels which can be reconfigured in orbit for both center frequency and bandwidth during the life-time of the satellite.